Risk Factors and Infection Patterns of Febrile Neutropenia after Induction Chemotherapy in Patients with Acute Myeloid Leukemia - Pratiwi, Made Sindy Astri; Agustini, Made Priska Arya; Rena, Ni Made Renny Anggreni; Bakta, I Made (Indonesian Journal of Cancer, 2026)
Background: Febrile neutropenia (FN) is a serious cause of mortality in acute myeloid leukemia (AML), with a mortality rate of 10-30%. FN often occurs after receiving induction chemotherapy in AML. Patients with FN are susceptible to various infections, but the pathogens are often unknown. It is important to predict FN and identify the specific pathogen of infection. This study aims to identify risk factors and infection patterns of FN after induction chemotherapy in AML patients.Methods: This research was a retrospective cohort study located at Prof. I.G.N.G Ngoerah General Hospital, Bali. The samples were AML patients aged ≥ 18 years treated with induction chemotherapy, cytarabine plus daunorubicin, from 2018 to 2022. The risk factors assessed were age, gender, body mass index, ECOG status, comorbidity, and pre-treatment blood count. The patients who had FN would be assessed for the incidence of infection through microbiological examination.Results: This study included 92 patients aged 19 to 76 years old. As many as 68 patients (73.9%) had FN. A multivariate analysis showed ECOG status (p = 0.004; OR 6.680; 95% CI 1.830 – 24.385), comorbidity (p = 0.010; OR 7.394; 95% CI 1.628 – 33.575), and haemoglobin level ≤ 8 g/dL (p = 0.015; OR 6.043; 95% CI 1.449 – 33.265) as significant risk factors. The most common site of infection was the respiratory tract (63.75%), followed by genitourinary (15%) and skin (8.75%). Most specimens were obtained from sputum (35%), blood (26.25%), and urine (15%). Streptococcus sp., Staphylococcus sp., and Escherichia coli were the top three most common pathogens found. Conclusions: ECOG status, comorbidity, and low haemoglobin level were associated with FN after induction chemotherapy of AML. Patients with FN are susceptible to various infections. The identification of risk factors and infections of FN will facilitate consideration of further treatment in AML.